Learning Mixture Models of Images and Inferring Spatial Transformations Using the EM algorithm - Frey, Brendan; Jojic, Nebojsa (IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 1999., 1999)
Mixture modeling and clustering algorithms are effective, simple ways to represent images using a set of data centers. However, in situations where the images include background clutter and transformations such as translation, rotation, shearing and warping, these methods extract data centers that include clutter and represent different transformations of essentially the same data. Taking face images as an example, it would be more useful for the different clusters to represent different poses and expressions, instead of cluttered versions of different translations, scales and rotations. By including clutter and transformation as unobserved, latent variables in a mixture model, we obtain a new "transformed mixture of Gaussians", which is invariant to a specified set of transformations. We show how a linear-time EM algorithm can be used to fit this model by jointly estimating a mixture model for the data and inferring the transformation for each image. We show that this algorithm can jointly align images of a human head and learn different poses. We also find that the algorithm performs better than k-nearest neighbors and mixtures of Gaussians on handwritten digit recognition.